Postoperative care of the newborn with myelomeningocele - (:unkn) unknown (Springer Milan, 2008)
Failure of the neural tube to close is potentially one of the most devastating and severely disabling congenital malformations of the newborn. Of these lesions, myelomeningocele (MMC) comprises 98.8% of open spinal dysraphism [1]. Myelomeningocele has been described as the most complex treatable, congenital anomaly consistent with life [2]. This squarely places the onus of successful treatment onto the multidisciplinary team of caregivers who will manage the diagnosis, repair, postoperative care and follow-up of children with MMC. Management of neonates with MMC is multifaceted. Various organ systems including the skeletal, muscular, urological, respiratory, skin and central nervous system are involved. This involvement of so many different organ systems results in interrelated problems requiring immediate and long-term consultation from a variety of different medical specialties. Compared with the treatment of older children, neurosurgical treatment of these neonates is extraordinarily complex. The neonate has limited pulmonary, cardiac, renal, nutritional and thermoregulatory reserves, is more susceptible to infection and has an altered metabolic response to operative stress [3]. © 2008 Springer-Verlag Italia.